2011
DOI: 10.1523/jneurosci.6066-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Reconsolidation or Extinction: Transcription Factor Switch in the Determination of Memory Course after Retrieval

Abstract: In fear conditioning, aversive stimuli are readily associated with contextual features. A brief reexposure to the training context causes fear memory reconsolidation, whereas a prolonged reexposure induces memory extinction. The regulation of hippocampal gene expression plays a key role in contextual memory consolidation and reconsolidation. However, the mechanisms that determine whether memory will reconsolidate or extinguish are not known. Here, we demonstrate opposing roles for two evolutionarily related tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 54 publications
2
90
0
Order By: Relevance
“…On this matter, conflicting results have been reported using different paradigms, with some studies showing facilitation of conditioning by FK-506 (de la Fuente et al 2014), antisense DNA against genes coding for the catalytic subunits of CaN (Ikegami and Inokuchi 2000), and transgenic inhibition of CaN (Malleret et al 2001;Baumgärtel et al 2008;Havekes et al 2008) and others finding no effect of the latter intervention (Zeng et al 2001). Still, in accordance with our results, most of these studies have found that the transgenic (Baumgärtel et al 2008; Havekes It should be noted that, unlike what occurred in our study, some of these previous investigations (de la Fuente et al 2011;Merlo et al 2014) did find an effect of calcineurin inhibition on long-term extinction. This disparity could be due to methodological differences such as different animal species or strains, different behavioral protocols, or different sites of CaN inhibition.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…On this matter, conflicting results have been reported using different paradigms, with some studies showing facilitation of conditioning by FK-506 (de la Fuente et al 2014), antisense DNA against genes coding for the catalytic subunits of CaN (Ikegami and Inokuchi 2000), and transgenic inhibition of CaN (Malleret et al 2001;Baumgärtel et al 2008;Havekes et al 2008) and others finding no effect of the latter intervention (Zeng et al 2001). Still, in accordance with our results, most of these studies have found that the transgenic (Baumgärtel et al 2008; Havekes It should be noted that, unlike what occurred in our study, some of these previous investigations (de la Fuente et al 2011;Merlo et al 2014) did find an effect of calcineurin inhibition on long-term extinction. This disparity could be due to methodological differences such as different animal species or strains, different behavioral protocols, or different sites of CaN inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…This disparity could be due to methodological differences such as different animal species or strains, different behavioral protocols, or different sites of CaN inhibition. In these previous studies, which used inbred C57BL/6 mice (de la Fuente et al 2011) and rats (Merlo et al 2014), animals were trained in an auditory fear conditioning paradigm, even though they were tested for contextual fear conditioning in de la Fuente et al (2011). Furthermore, in these studies CaN was inhibited locally in the hippocampus by FK-506 (de la Fuente et al 2011) or in the amygdala by an antisense oligodeoxynucleotide (Merlo et al 2014), a fact that might also account for the observed disparities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, some opposing molecular mechanisms in the hippocampus underlie these two processes. For example, hippocampal CREB and NF-kB are activated by reconsolidation but not by extinction (de la Fuente et al, 2011;Mamiya et al, 2009), suggesting that some specific mechanism determines the memory process after retrieval.…”
Section: Role Of Hippocampal Ne In the Persistence Of Extinction Ltmmentioning
confidence: 99%